Anxiolytic-like effects of YL-IPA08, a potent ligand for the translocator protein (18 kDa) in animal models of post-traumatic stress disorder. (24th April 2014) - Zhang, Li-Ming; Qiu, Zhi-Kun; Zhao, Nan; Chen, Hong-Xia; Liu, Yan-Qin; Xu, Jiang-Ping; Zhang, You-Zhi; Yang, Ri-Fang; Li, Yun-Feng
Abstract: Recently, the translocator protein (18 kDa) (TSPO), previously called peripheral benzodiazepine receptor (PBR) and both the starting point and an important rate-limiting step in neurosteroidogenesis, has received increased attention in the pathophysiology of post-traumatic stress disorder (PTSD) because it affects the production of neurosteroids, reinforcing the hypothesis that selective TSPO ligands could potentially be used as anti-PTSD drugs. As expected, we showed that chronic treatment with YL-IPA08 [N-ethyl-N-(2-pyridinylmethyl)-2-(3, 4-ichlorophenyl)-7-methylimidazo [1, 2-a] pyridine-3-acetamide hydrochloride], a potent and selective TSPO ligand synthesized by our institute, caused significant suppression of enhanced anxiety and contextual fear induced in the inescapable electric foot-shock-induced mouse model of PTSD and the time-dependent sensitization (TDS) procedure. These effects were completely blocked by the TSPO antagonist PK11195. Furthermore, YL-IPA08 could increase the level of allopregnanolone in the prefrontal cortex and serum of post-TDS rats, and these effects were antagonized by PK11195. In summary, the findings from the current study showed that YL-IPA08, a potent and selective TSPO ligand, had a clear anti-PTSD-like effect, which might be partially mediated by binding to TSPO and the subsequent synthesis of allopregnanolone.